NALAR KEBERAGAMAAN MASYARAKAT BANJAR: DARI MISTIS-REALIS HINGGA TRADISIONALIS-KRITIS - Nadhiroh, Wardatun (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2019)
The Banjar community, which consists of the Banjar ethnic group, is referred to as a tribe that overlaps between ethnic and religious identities. When mentioned with the word "Banjar", it will be imagined the word "Islam" accompanies it. The inherent stamp of "Banjar Islam" shows a certain religious dimension in it which is certainly different from other Muslims. This article is presented to illustrate the typology of religious reasoning of Banjar people who are associated with the label of Banjar Islam in front of them. It should be noted that far from the arrival of Islam, Banjar people also developed the belief in animism-dynamism followed by Hinduism and Buddhism. It was thanks to the role of the Banjar Sultanate that the Banjar community became the Banjar Islam. In the end, a shift in reason also occurred in the religious constructs of the Banjar community in line with social changes. This paper is a literature study that relies on descriptive methods in its presentation and psycho-socio-historical approach as the knife of analysis. This article explains that there are at least 4 types of reasoning that developed in Banjar since the era of animism and dynamism until after the entry of religious movements in the 20th century, namely mystical-realist, mystical-idealist, literalist-normative, and traditionalist-critical. The development of the religious reasoning of the Banjar community did not occur linearly, but rather overlapping.Masyarakat Banjar yang terdiri dari etnis Banjar disebut sebagai suku yang bertumpang-tindih antara identitas kesukuan dan identitas keagamaannya. Ketika disebutkan dengan kata Banjar, maka akan terbayang kata Islam menyertainya. Cap ?Islam Banjar? yang melekat menunjukkan adanya suatu dimensi keberagamaan tertentu di dalamnya yang tentunya berbeda dengan Islam-Islam lainya. Artikel ini dihadirkan untuk menggambarkan tipologi nalar beragama masyarakat Banjar dikaitkan dengan adanya label Islam Banjar di depannya. Perlu diketahui bahwa jauh kedatangan Islam, di Banjar pun juga berkembang kepercayaan animisme-dinamisme yang disusul agama Hindu dan Buddha. Berkat peran kesultanan Banjarlah masyarakat Banjar menjadi Islam Banjar. Pada akhirnya, pergeseran nalar pun juga terjadi dalam konstruk keberagamaan masyarakat Banjar seiring perubahan sosial kemasyarakatan. Tulisan ini adalah kajian kepustakaan yang mengandalkan metode deskriptif dalam pemaparannya dan pendekatan psiko-sosio-historis sebagai pisau analisisnya. Artikel ini menjelaskan bahwa setidaknya ada 4 tipologi nalar yang berkembang sejak animisme dan dinamisme hingga pasca masuknya gerakan keagamaan di abad 20, yaitu mistis-realis, mistis idealis, literalis normatif, dan tradisionalis-kritis. Perkembangan nalar kekeberagamaan masyarakat Banjar tidak terjadi evolusi linier, namun lebih bersifat overlapping.